Composition and Oxidation Dependence of Glass Transition in Epoxy Asphalt. Issue 11 (November 2021) - Apostolidis, Panos; Liu, Xueyan; Erkens, Sandra; Scarpas, Tom
Miscibility, and lack of it, is decisive for durable polymer-modified asphalt binders and reflects the long-term performance of asphalt materials in terms of fatigue and thermal cracking. In this work, the glass transition behavior of epoxy asphalt will be assessed extensively after different oxidative aging time periods using differential scanning calorimetry. The composition dependence of glass transition in epoxy asphalt binders over oxidative aging is evaluated by emphasizing the deviation of glass transition temperature ( Tg ) with the change in sign and magnitude. An entropy-based analysis of glass transitions in epoxy asphalt is discussed as well. The blends formulated by epoxy and asphalt binder have shown an increase of the Tg deviation from the ideal mixing rule over oxidative aging. Two different shapes of the composition dependence of the Tg values are observed between the blends with and without fillers but showing both distinct positive deviations from the case of mixing ideal materials. The Tg and heat capacity ( Cp ) parameters determined in relation to the epoxy asphalt composition provide insights into the effect of limestone fillers on the oxidation-induced embrittlement of epoxy asphalt materials. The results could help select the epoxy proportion in asphalt to develop super-durable and long-lasting pavement materials.